Brand fans : lessons from the world's greatest sporting brands - Smith, Aaron, 1972-; Stavros, Constantino; Westberg, Kate (Palgrave Macmillan, 2017)
Combining the latest branding research with a diverse range of powerful case examples, this book reveals the cutting edge techniques of value co-creation, personalisation and customer engagement employed by sport's leading brands. Based on the transferable lessons that emanate from these practices, Brand Fans explores and illuminates how firms can cultivate connected fans and lifelong advocates, while building brand equity exponentially in the process. This is a book that will appeal to scholars and practitioners alike, as well as anyone fascinated by modern marketing, consumer relationships and branding.
Keywords: Branding (Marketing); Sports -- Marketing.; Brand loyalty -- Case studies.; elektronické knihy; electronic books